Water harvesting cube - M. Salim Ferwati (8407596) (2019)
Water scarcity is at the center of the world’s greatest challenges, including famine, disease, and sustainable development. In many countries, there are active researches aimed at improving the supply of fresh water through actions such as seawater desalination and water recycling. Researchers are also working, on a smaller scale, to harvest water from the atmosphere to serve individual households or small communities. Cool surface condensation, fog catchers, and humidity harvesting are three examples of sustainable approaches that relied on affordable and simple equipment. This paper aims to introduce the possibility of using water condensation to generate potable water by using a self-sustainable-energy device. The device is scalable; being able to meet the needs of a single household and up to a residential district. The focus of this research is on the function of a water-harvesting cube. It consists of a set of solar panels, an energy converter, a dehumidifier(s), a water treatment component, and a water storage tank. The sum of all parts forms a 1 × 1 × 1 m cube. The premise of the proposal is that one dehumidifier can produce a sufficient amount of pure water for an individual’s various daily uses. The researcher conducted two experiments during the summer of 2018, one in London, Ontario, Canada, and the other in Doha, Qatar. The result showed that in an environment of 50–70% relative humidity, a single dehumidifier could produce up to 15 L of pure water per day. The research here proves that the proposed water harvesting cube is efficient, affordable, and requires low maintenance. Other Information Published in: SN Applied Sciences License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42452-019-0730-y